International Steam Tables Properties of Water and Steam based on the Industrial Formulation IAPWS-IF97 - Kretzschmar, Hans-Joachim; Wagner, Wolfgang (Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2019)
This book contains steam tables for practical industrial use calculated by using the international standard IAPWS-IF97 for the thermodynamic properties of water and steam and the IAPWS industrial standards for transport and other properties. The complete set of equations of IAPWS-IF97 is presented including all supplementary backward equations adopted by IAPWS for fast calculations of heat cycles, boilers, and steam turbines. The calculation of the properties is not only shown for the usual input parameter pairs pressure and temperature, but also for the parameters pressure and enthalpy, pressure and entropy, enthalpy and entropy. It is for the first time that such a description is given. For designing advanced energy conversion processes, tables and property calculation algorithms of steam up to 2000 °C are given. In addition, these steam tables contain the following features: • Formulas to calculate arbitrary partial derivatives of the eightmost important properties from IAPWS-IF97, which are very helpful in non-stationary process modelling, are shown. • The uncertainty values of IAPWS-IF97 regarding the most important properties are included. • Pressure-temperature diagrams with isolines of 26 thermodynamic, transport and other properties are added. Hans-Joachim Kretzschmar is Professor at the Faculty of Mechanical Engineering at the Zittau/Goerlitz University of Applied Sciences. He is specialized in the calculation of the properties for working fluids in heat cycles, boilers, and turbines. Prof. Kretzschmar was involved in the development of the industrial standard IAPWS-IF97. As chairman of the Task Group on "Supplementary Backward Equations for the Industrial Formulation IAPWS-IF97" he has coordinated the development of further backward equations for thermodynamic process modelling. Prof. Kretzschmar is an active member of the International Association for the Properties of Water and Steam (IAPWS). He served as a chair of the IAPWS Working Group "Thermophysical Properties of Water and Steam" (TPWS) from 2006 to 2011. From 2011 to 2016, he was chair of the IAPWS German National Committee. For the period from 2016 to 2018, he was elected as President of IAPWS. In 2012 he received the Honorary Fellow Award of IAPWS and in 2018 the Education Award of the State Saxony. Wolfgang Wagner is Professor Emeritus at the Chair of Thermodynamics at the Ruhr-University Bochum. His scientific working field covers the thermophysical properties of pure fluids and mixtures (gases and liquids), in particular multi-parameter equations of state and highly-accurate density measurements over large ranges of temperature, pressure, and density. His research works have resulted in about 200 publications including fife books. Prof. Wagner is an active member of the International Association of the Properties of Water and Steam (IAPWS). Under his supervision, the "IAPWS Formulation 1995 for the Thermodynamic Properties of Ordinary Water Substance for General and Scientific Use" (IAPWS-95) and the "IAPWS Industrial Formulation 1997 for the Thermodynamic Properties of Water and Steam" (IAPWS-IF97) were developed. In 1998 he received the Honorary Fellow Award of IAPWS and in 2003 the Yeram S. Touloukian Award of the American Society of Mechanical Engineers (ASME). In 2008 he received the Gibbs Award of the International Association of the Properties of Water and Steam. In 2015, Prof. Wagner was bestowed the title "honorary doctor" by the Dresden University of Technology.